HUBUNGAN AKTIVITAS FISIK DAN KUANTITAS TIDUR DENGAN KEJADIAN HIPERTENSI - Gusnilawati, Gusnilawati (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
Hypertension is not a contagious disease that is a cause of death in the world .Approximately 17.5 million people worldwide die from hypertension . An estimated 2025cases of hypertension will be 1.6 billion cases of hypertension . The cause of hypertension isdivided into two factors that can be controlled and uncontrolled . Controlled factors , amongothers, excessive salt intake , cholesterol , smoking , alcohol , physical activity , quantity ofsleep , lifestyle , stress , and obesity . This study was to determine the relationship of physicalactivity and quantity of sleep with the incidence of hypertension in Puskesmas SukamerinduBengkulu .This type of research is the use of cross -sectional and sampling methodsperformed with accidental sampling technique . The number of samples of this study were 97respondents and data collection was done by questionnaire interview . This study analyzesusing univariate and bivariate analysis with the Chi - Square test statistic where the significantlevel p = 0.05The results of the study demonstrate a significant association between physicalactivity with incidence of hypertension with p = 0:00 and a significant correlation with theincidence of sleep quantity with hypertension incidence with p = 0:00 .PHC nurses expectedfurther improve the quality of health services, especially in patients at risk for hypertensionand preventive improvement can be done by preventing the increase in hypertension .